Regulation of miRNA expression in the prefrontal cortex by fecal microbiota transplantation in anxiety-like mice - Chen, Simin; Li, Mengjia; Tong, Changqing; Wang, Yanan; He, Jiahui; Shao, Qi; Liu, Yan; Wu, Ying; Song, Yuehan (Frontiers in Psychiatry, 2024)
Background: The gut-brain axis and gut microbiota have emerged as key players in emotional disorders. Recent studies suggest that alterations in gut microbiota may impact psychiatric symptoms through brain miRNA along the gut-brain axis. However, direct evidence linking gut microbiota to the pathophysiology of generalized anxiety disorder (GAD) via brain miRNA is limited. In this study, we explored the effects of fecal microbiota transplantation (FMT) from GAD donors on gut microbiota and prefrontal cortex miRNA in recipient mice, aiming to understand the relationship between these two factors. Methods: Anxiety scores and gut microbiota composition were assessed in GAD patients, and their fecal samples were utilized for FMT in C57BL/6J mice. Anxiety-like behavior in mice was evaluated using open field and elevated plus maze tests. High-throughput sequencing of gut microbiota 16S rRNA and prefrontal cortex miRNA was performed. Results: The fecal microbiota of GAD patients exhibited a distinct microbial structure compared to the healthy group, characterized by a significant decrease in Verrucomicrobia and Akkermansia, and a significant increase in Actinobacteria and Bacteroides. Subsequent FMT from GAD patients to mice induced anxiety-like behavior in recipients. Detailed analysis of gut microbiota composition revealed lower abundances of Verrucomicrobia, Akkermansia, Bifidobacterium, and Butyricimonas, and higher abundances of Deferribacteres, Allobaculum, Bacteroides, and Clostridium in mice that received FMT from GAD patients. MiRNA analysis identified five key miRNAs affecting GAD pathogenesis, including mmu-miR-10a-5p, mmu-miR-1224-5p, mmu-miR-218-5p, mmu-miR-10b-5p, and mmu-miR-488-3p. Notably, mmu-miR-488-3p showed a strong negative correlation with Verrucomicrobia and Akkermansia.This study demonstrates that anxiety-like behavior induced by human FMT can be transmitted through gut microbiota and is associated with miRNA expression in the prefrontal cortex. It is inferred that the reduction of Akkermansia caused by FMT from GAD patients leads to the upregulation of mmu-miR-488-3p expression, resulting in the downregulation of its downstream target gene Creb1 and interference with its related signaling pathway. These findings highlight the gut microbiota's crucial role in the GAD pathophysiology.